The association between elevated serum uric acid levels and islet β-cell function indexes in newly diagnosed type 2 diabetes mellitus: a cross-sectional study - Yimeng Hu; Jie Liu; Huiqiong Li; Hui Zhu; Linjie Liu; Yin Yuan; Jing Chen; Ye Wang; Xuemei Hu; Yancheng Xu (PeerJ, 2018)
Background Serum uric acid (UA) has been reported as a risk factor for type 2 diabetes mellitus (T2DM). However, whether serum UA is associated with insulin resistance and insulin secretion, and the effect of gender on it in the case of the existed association, both remain undefined. Methods A cross-sectional study was designed and performed, which enrolled a total of 403 newly diagnosed T2DM patients (mean age, 50.21 ± 13.34 years (62.5% males)). Clinical characteristics and islet function indexes of all participants were analyzed based on gender-specific tertiles of serum UA levels. In addition, multiple linear regression analysis was conducted to investigate covariates associated with islet function indexes. Results The mean levels of serum UA were 331.05 μmol/L (interquartile range (IQR): 60.6, 400.9 μmol/L) and 267.9 μmol/L (IQR: 204.7, 331.9 μmol/L) in men and women, respectively. The values of insulin secretion indexes involving AUCins30/glu30, AUCins120/glu120 and total insulin disposition index (DI120) in females were significantly higher than those in males. Apart from the homeostasis model assessment insulin resistance of men, serum UA was positively associated with insulin secretion and insulin resistance indexes both in men and women. Multivariable linear regression analysis showed serum UA exerted an independent impact on insulin secretion in females, but not on insulin resistance. In males, islet function was simultaneously affected by serum UA age, body mass index (BMI), and serum lipids. Conclusion Serum UA harbored a positive correlation with insulin secretion and insulin resistance indexes in newly diagnosed T2DM patients, which was influenced by gender, BMI, serum lipids. Hence, serum UA may be considered as a predictor for islet function in clinical practice.